2019
DOI: 10.3171/2018.8.spine18197
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted intravertebral augmentation corrects local kyphosis more effectively than a conventional fluoroscopy-guided technique

Abstract: OBJECTIVEIntravertebral augmentation (IVA) is a reliable minimally invasive technique for treating Magerl type A vertebral body fractures. However, poor correction of kyphotic angulation, the risk of cement leakage, and significant exposure to radiation (for the surgeon, the operating room staff, and the patient) remain significant issues. The authors conducted a study to assess the value of robot-assisted IVA (RA-IVA) for thoracolumbar vertebral body fractures. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Han et al 20 reported that the operation time of RA thoracolumbar spine internal fixation surgery was 149.5 + 50.8 mins, which was slightly longer than that of the FA of 138.0 + 48.6 mins, but there was no statistical difference between the 2 methods. However, Alsalmi et al 21 reported that RA intravertebral augmentation was 52 + 11 mins, which was significantly longer than that of C-arm assisted surgery of 30 + 11 mins. In this study, the operation time of RA surgery for single segment fractures was significantly longer than that of the FA surgery.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Han et al 20 reported that the operation time of RA thoracolumbar spine internal fixation surgery was 149.5 + 50.8 mins, which was slightly longer than that of the FA of 138.0 + 48.6 mins, but there was no statistical difference between the 2 methods. However, Alsalmi et al 21 reported that RA intravertebral augmentation was 52 + 11 mins, which was significantly longer than that of C-arm assisted surgery of 30 + 11 mins. In this study, the operation time of RA surgery for single segment fractures was significantly longer than that of the FA surgery.…”
Section: Discussionmentioning
confidence: 96%
“…In other navigation technique assisted PKP studies, the VAS improved dramatically after surgery without difference compared with FA group. 21,22 Radiation exposure during operation is an occupational risk for orthopedic surgeons. Mastrangelo et al 27 found that orthopedic surgeons have a high incidence of tumor due to radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations